2018
DOI: 10.1002/1873-3468.12995
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase‐3β regulation: another kinase gets in on the AKT

Abstract: Read the Original article at doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Downstream of Akt pathway, GSK3β is a crucial protein involved in cell signaling. In Akt pathway, the regulation of adipogenesis is accomplished via the phosphorylation Ser9 and inactivation of GSK3β resulting in the decreased phosphorylation and inactivation of β‐catenin, C/EBPα, and GS (Turk, ). Some studies have reported that overactive GSK3β is related to some metabolic disorders, such as type 2 diabetes and obesity (Yen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Downstream of Akt pathway, GSK3β is a crucial protein involved in cell signaling. In Akt pathway, the regulation of adipogenesis is accomplished via the phosphorylation Ser9 and inactivation of GSK3β resulting in the decreased phosphorylation and inactivation of β‐catenin, C/EBPα, and GS (Turk, ). Some studies have reported that overactive GSK3β is related to some metabolic disorders, such as type 2 diabetes and obesity (Yen et al, ).…”
Section: Discussionmentioning
confidence: 99%